ADAPTIVE NOISE CANCELING MENGGUNAKAN ALGORITMA LEAST MEAN SQUARE (LMS) - Nardiana, Anita; Sumaryono, Sari Sujoko (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2011)
Noise is inevitable in communication system. In some cases, noise can disturb signal. It is veryannoying as the received signal is jumbled with the noise itself. To reduce or remove noise, filter lowpass,highpass or bandpass can solve the problems, but this method cannot reach a maximum standard. One ofthe alternatives to solve the problem is by using adaptive filter. Adaptive algorithm frequently used is LeastMean Square (LMS) Algorithm which is compatible to Finite Impulse Response (FIR). The positive result ofthis experiment can be seen from the value of Mean Square Error (MSE) and Signal to Noise Ratio (SNR).Keyword : Noise, adaptive filter, Least Mean Square (LMS), Mean Square Error (MSE)